A new species of the genus Lamellitettigodes (Orthoptera: Tetrigidae) from PR China, with taxonomic notes on the genus - Lu, Yong-Zhong; Zha, Ling-Sheng (Zootaxa, 2020)
Two species of the pygmy grasshopper genus Lamellitettigodes Günther are described: Lamellitettigodes diversifemoris Lu & Zha sp. n. from Hainan, and Lamellitettigodes sagittatus (Bolívar) from Hainan and Yunnan, PR China. Both species are photographed and compared with their allies. Taxonomic changes are proposed: Lamellitettigodes bimaculatus (Zheng) comb. nov. is transferred from Euparatettix bimaculatus Zheng, and Euparatettix tuberifemora Deng, Zheng & Wei syn. nov. is synonymized with Lamellitettigodes sagittatus. Lamellitettigodes and its allied genera, Euparatettix, Paratettix, Hedotettix, Tetrix and Ergatettix are compared with each other, and useful diagnostic characters for them are recommended. An updated species key for Lamellitettigodes is provided.